Response of Application of Lime and Inorganic Phosphorus Fertilizer on Yield and Yield Related Traits of Upland Rice (Oryza sativa L) at Assosa, Benishangul Gumuz Region - Boru, Merga; Misgana, Mathewos (International Journal of Applied Sciences and Biotechnology, 2025)
In Benishangul gumuz region, a field experiment was carried out to ascertain the impact of application of lime and inorganic phosphorus fertilizer on rice yield and yield components in 2019 and 2020 cropping years at Bambassi district. Experiments were conducted to evaluate the response of lime and and Phosphorus fertilizer application to rice crop around Bambassi area. Four levels of lime (0, 1.99, 3.98, and 5.97 t ha-1) and five levels of P (0, 23, 46, 69 and 92 kg ha-1) laid out in randomized complete block design in factorial arrangement with three replications. Analysis of variance revealed that the interaction effect of lime and phosphorus fertilizer significantly (P≤0.05) affected plant height, dry biomass, and grain yield of rice crop. Panicle length, straw yield, and harvest index were affected by the main effect of application of lime and phosphorus. The highest grain yield (4.43 t ha-1) of rice was obtained from 5.97 t lime ha- 1 with application of 92 kg P2O5 ha-1 treatments. But partial budget analysis indicted that 1.99 t lime ha-1 along with 46 kg P2O5 ha-1 gave higher net benefits (ETB 211,700ha-1). Thus, farmers growing rice in the research areas can be advised to use combined applications 1.99 t lime ha-1 with application of 92kg P2O5 ha-1.Int. J. Appl. Sci. Biotechnol. Vol 13(1): 31-37.